2013
DOI: 10.1111/imj.12174
|View full text |Cite
|
Sign up to set email alerts
|

Early prosthetic hip joint infection treated with debridement, prosthesis retention and biofilm‐active antibiotics: functional outcomes, quality of life and complications

Abstract: Key words

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 20 publications
1
41
1
2
Order By: Relevance
“…A total of 11 studies reporting on 292 cases could be identified ( Figure 1) [2][3][6][7][8][9][10][11][12][13][14] . Two studies were published before and nine after 2000.…”
Section: Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 11 studies reporting on 292 cases could be identified ( Figure 1) [2][3][6][7][8][9][10][11][12][13][14] . Two studies were published before and nine after 2000.…”
Section: Researchmentioning
confidence: 99%
“…One study [10] reported on debridement and another on debridement and irrigation [12] . Six studies performed debridement, lavage and change of modular prosthesis components (polyethylene (PE) liner, femoral stem head) [2,3,6,7,9,14] , whereas in one of these studies the PE liner was not changed in all patients [9] . One study combined this procedure along with the use of the vacuum-assisted closure therapy [11] .…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations